Doing More with Less: Complex Meningiomas Illustrative Case Series - Tagle-Vega, Uriel; Vera-Torres, Lucero; Medina-Mendez, Monserrat; Choque-Velasquez, Joham (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
The present study addresses the challenges of treating complex meningiomas in a low- to middle-income country (L-MIC) with limited access to advanced surgical equipment. The objective is to present innovative low-cost approaches and surgical techniques employed in the absence of a neurosurgical microscope, emphasizing resourcefulness in addressing surgical challenges.The senior author conducted surgical interventions on four patients with complex meningiomas in a middle-income country's grade III hospital. Due to resource limitations, surgeries did not utilize a neurosurgical microscope. Instead, the Modified Pure Endoscopic Approach (MAPEnd) technique, intratumoral hydrogen peroxide infiltration, and water dissection were employed for intraoperative vision and magnification support. Thorough preoperative planning was crucial for successful treatment.The case series includes four illustrative cases ranging from parietal and posterior fossa giant meningiomas to front-parietal and cerebellopontine angle large meningiomas. Despite the limitations, effective tumor resections and favorable patient outcomes were achieved.In resource-limited settings, where access to advanced neurosurgical equipment is constrained, this study demonstrates the successful treatment of complex meningiomas. The combination of water dissection, intratumoral hydrogen peroxide injection, and the MAPEnd method, along with meticulous preoperative planning, promises favorable surgical outcomes. These techniques contribute to neurosurgical innovation and bridge the gap in providing quality surgical care in L-MICs.
Keywords: meningioma; global neurosurgery; LMICs; resource-limited settings; low-cost techniques